Methodological and Methodical Principles of the Empirical Study of Spiritual Development of a Personality - Klymyshyn, Olga; Karpenko, Hanna (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
The article reveals the essence of the methodological principles of the spiritual development of a personality. The results of the theoretical analysis of psychological content of spirituality from the positions of system and structural approach to studying of a personality, age patterns of the mental personality development, the sacramental nature of human person, mechanisms of human spiritual development are taken into consideration. The interpretation of spirituality and the spiritual development of a personality is given. Initial principles of the organization of the empirical research of the spiritual development of a personality (ontogenetic, sociocultural, self-determination, system) are presented. Such parameters of the estimation of a personality’s spiritual development as general index of the development of spiritual potential, indexes of the development of ethical, aesthetical, cognitive, existential components of spirituality, index of religiousness of a personality are described. Methodological support of psychological diagnostic research is defined